1992
DOI: 10.1038/ng1292-292
|View full text |Cite
|
Sign up to set email alerts
|

Charcot–Marie–Tooth type 1A duplication appears to arise from recombination at repeat sequences flanking the 1.5 Mb monomer unit

Abstract: We have constructed a 3.1 megabase (Mb) physical map of chromosome 17p11.2-p12, which contains a submicroscopic duplication in patients with Charcot-Marie-Tooth disease type 1A (CMT1A). We find that the CMT1A duplication is a tandem repeat of 1.5 Mb of DNA. A YAC contig encompassing the CMT1A duplication and spanning the endpoints was also developed. Several low copy repeats in 17p11.2-p12 were identified including the large (> 17 kb) CMT1A-REP unit which may be part of a mosaic repeat. CMT1A-REP flanks the 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
222
0
4

Year Published

1993
1993
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 352 publications
(226 citation statements)
references
References 42 publications
0
222
0
4
Order By: Relevance
“…Roughly half of these patients have CMT1A,2 a demyelinating neuropathy caused by a 1.4‐Mb duplication in chromosome 17p12 that contains the peripheral myelin protein 22 gene, PMP22 , an integral membrane protein expressed in PNS compact myelin 3, 4. CMT1A is hypothesized to occur as a result of nonallelic homologous recombination (NAHR)5, 6, 7 in a region of 17p12 surrounding and including the PMP22 gene, causing increased expression of the normal gene product.…”
Section: Introductionmentioning
confidence: 99%
“…Roughly half of these patients have CMT1A,2 a demyelinating neuropathy caused by a 1.4‐Mb duplication in chromosome 17p12 that contains the peripheral myelin protein 22 gene, PMP22 , an integral membrane protein expressed in PNS compact myelin 3, 4. CMT1A is hypothesized to occur as a result of nonallelic homologous recombination (NAHR)5, 6, 7 in a region of 17p12 surrounding and including the PMP22 gene, causing increased expression of the normal gene product.…”
Section: Introductionmentioning
confidence: 99%
“…In proximal 17p, for example, LCRs account for more than 23% of the genomic sequence, making this region a hotspot for NAHR [8]. Among the well-studied constitutional genomic disorders and rearrangements caused by LCRs in proximal 17p are the Charcot-Marie-Tooth disease type 1A duplication [9] and its reciprocal deletion, identified in patients with hereditary neuropathy with liability pressure palsies [10], and the SmithMagenis syndrome deletion and its reciprocal duplication, dup(17)(p11.2 p11.2) [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A duplication on chromosome 17p12 was identified as the basis of Charcot-Marie-Tooth disease type 1 (CMT1A) (Lupski et al, 1991), whereas an interstitial deletion including the PMP22 gene was observed in patients with Hereditary Neuropathy with Liability to Pressure Palsies (HNPP) (Chance et al, 1993). These distinct conditions represent prototypical disorders for the elucidation of the mechanism responsible for genomic disorders, as low copy repeats (LCRs) were identified in the region involved and nonallelic homologous recombination (NAHR) using these repeats as recombination substrates results in either the duplication or deletion (Pentao et al, 1992;Chance et al, 1994, Reiter et al, 1996Reiter et al, 1998).…”
Section: Charcot-marie-tooth Disease -Human Hereditary Neuropathy Witmentioning
confidence: 99%